Weed control, soil health, and yield tradeoffs of between-bed management strategies in organic plasticulture vegetable production - Tarrant, Alyssa R.; Brainard, Daniel C.; Tiemann, Lisa K.; Hayden, Zachary D. (Frontiers in Sustainable Food Systems, 2024)
Planting a cover crop living mulch between plastic mulch beds in fresh market vegetable production can reduce soil erosion and runoff, and offers an opportunity to grow an income generating cash crop alongside a soil building cover crop. However, potential negative impacts on yield, variable weed control, unclear impacts on soil health, and limited management recommendations challenge adoption of this practice, despite grower interest. In a two-year study in southwest Michigan, living mulches were evaluated in the production of plasticulture organic summer squash (Cucurbita pepo cv. Lioness) and bell pepper (Capsicum annuum cv. Paladin). Strategies evaluated included three common grower practices (cultivation, dead straw mulch, mowing ambient weeds) and three mowed living mulch treatments (Italian ryegrass [Lolium multiflorum] monoculture, rye [Secale cereale] monoculture, and a Dutch white clover [Trifolium repens]/rye mixture). We determined the impact of these strategies on weed control, organic matter inputs, vegetable crop performance, nitrogen retention, and soil microbial communities. We found that cultivation and dead mulch provided superior in-season weed control, reducing weed biomass by an average of 86% compared to 18% among living mulch treatments, with associated reductions in the weed seedbank compared to living mulches and mowed weeds. In most cases, living mulch establishment was a challenge and weed biomass on average accounted for 99, 74, and 94% of organic matter inputs in rye, ryegrass, and clover/rye treatments, respectively. Squash performance was unaffected by our treatments, but pepper yield reductions ranged from 41 to 54% in all treatments relative to cultivation in one of two years. Living mulches and the weedy treatment showed the ability to reduce end-of-season potentially leachable nitrogen by 61% compared to cultivation and dead mulching. Soil microbial abundance and functional diversity were similar across treatments, but extracellular enzyme activity was higher in dead mulch, living mulch and weedy treatments compared to cultivation. Results from this study help quantify tradeoffs between common grower practices for managing weeds and soil between plastic mulch beds, highlight key challenges with living mulch alternatives, and identify areas for future research.